2000
DOI: 10.1115/1.1287161
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Deformation Levels Associated With Routine Physical Activity Are Less Stimulatory to Bone Cells Relative to Loading-Induced Oscillatory Fluid Flow

Abstract: Although it is well accepted that bone tissue metabolism is regulated by external mechanical loads, it remains unclear to what load-induced physical signals bone cells respond. In this study, a novel computer-controlled stretch device and parallel plate flow chamber were employed to investigate cytosolic calcium (Ca2+i) mobilization in response to a range of dynamic substrate strain levels (0.1-10 percent, 1 Hz) and oscillating fluid flow (2 N/m2, 1 Hz). In addition, we quantified the effect of dynamic substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
245
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(257 citation statements)
references
References 39 publications
7
245
0
5
Order By: Relevance
“…Note that the fluid flow to which osteocytes were exposed in this study is 2 hours. Several others studies (1,16,50,51,57) have shown that mechanical stimuli at this duration can induce many changes in markers of bone formation/resorption in bone cells. We expect that with longer flow exposure times, the bone resorption inhibition effect from mechanical loading might be further enhanced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the fluid flow to which osteocytes were exposed in this study is 2 hours. Several others studies (1,16,50,51,57) have shown that mechanical stimuli at this duration can induce many changes in markers of bone formation/resorption in bone cells. We expect that with longer flow exposure times, the bone resorption inhibition effect from mechanical loading might be further enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic fluid flow is one of the mechanical stimuli that osteocytes experience in vivo with habitual loading (24,25,54). Previous studies have established that this loading-induced dynamic fluid flow is a potent physical signal in the regulation of bone cell metabolism (7,16,37,57), yet it is unclear what role it might play in osteocyte mediated regulation of bone resorption.…”
Section: Introductionmentioning
confidence: 99%
“…Previous in vitro cell culture studies have established 10,000 µε in bone cells as a threshold above which an osteogenic response is stimulated (Burger and Veldhuijzen 1993b;You et al 2000). In order to determine whether changes in strain observed in our previous experimental study (Verbruggen et al 2015) could explore the possible mechanical properties in the computational model that could predict the observed experimental results.…”
Section: Parameter Variation Study Of Elastic Modulimentioning
confidence: 98%
“…It has been hypothesized that bone remodeling is controlled at the cellular level through signals mediated by osteocytes [25]. This hypothesis has been supported by results from in vitro experiments by You et al [26,27] in which bone cells were subjected to a fluid flow generated by shear stresses. The results of an in vivo experimental study by Vashishth et al [28] support the sensory role of osteocytes in human cortical bone and the decline of the osteocyte lacunar density caused by an accumulation of microcracks.…”
Section: Model Based On Ruptured Osteocyte Processes (Roc)mentioning
confidence: 95%